2016
DOI: 10.1371/journal.pone.0156121
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Short-Term Antiarrhythmic Drugs Use after Catheter Ablation of Atrial Fibrillation—A Systematic Review with Meta-Analyses and Trial Sequential Analyses of Randomized Controlled Trials

Abstract: BackgroundThe efficacy of short-term antiarrhythmic drugs (AADs) use compared with no-AADs prescription after catheter ablation of atrial fibrillation (AF) in preventing atrial arrhythmia recurrence is uncertain.MethodsWe searched PubMed, Embase, and the Cochrane Library through December 2015 to identify randomized controlled trials (RCTs) which evaluated the efficacy of short-term AADs use compared with no-AADs prescription after AF ablation in preventing atrial arrhythmia recurrence. The primary outcome was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
(88 reference statements)
1
13
0
Order By: Relevance
“…However, meta-analyses have shown that long-term ablation success remains unaffected by early AAD use[36-38]. This would suggest that AADs might mask the early indicators of failed ablation, which may be allowed to manifest only once AADs are withdrawn.…”
Section: Prevention Of Eraamentioning
confidence: 99%
“…However, meta-analyses have shown that long-term ablation success remains unaffected by early AAD use[36-38]. This would suggest that AADs might mask the early indicators of failed ablation, which may be allowed to manifest only once AADs are withdrawn.…”
Section: Prevention Of Eraamentioning
confidence: 99%
“…The following conclusion can be reached with TSA: if the cumulative z -curve crosses the trial sequential monitoring boundary or enters the futility area, a sufficient level of evidence for the anticipated intervention effect may have been obtained and no further trials are needed; if the z -curve does not cross any of the boundaries and the required information size has not been reached, the evidence is insufficient and more trials should be included to clarify this issue; and if the cumulative z -curve exceeds the estimated information size but does not cross the traditional monitoring boundary, the negative conclusion is sufficient and no further trial is required. [ 25 , 26 ]…”
Section: Methodsmentioning
confidence: 99%
“…Two recent meta-analyses concluded that anti-arrhythmic drug use after catheter ablation for atrial fibrillation reduced early arrhythmia recurrence but did not prevent late recurrence of atrial arrhythmias. 117,118 A randomized trial of anti-arrhythmic drug treatment after surgical ablation demonstrated reduced early recurrence of atrial arrhythmias in the treatment arm. 119 Any correlation between post-ablation recurrence, drug therapy and biomarkers is not well elucidated.…”
Section: 116mentioning
confidence: 99%